Mr Men The Big Bump - Hargreaves, Roger; Hargreaves, adam (London Egmont, 2016)
The Mr. Men and Little Miss are here to help engage children and inspire them to read with confidence. This book includes two funny stories about perhaps the most unfortunate Mr. Men characters - Mr. Bump and Mr. Messy! With colourful pictures, short sentences and simple, phonetic-based vocabulary, children will love learning to read with the Mr. Men and Little Miss. Level 1 Reading Ladder titles are perfect for new readers who are beginning to read simple stories with help
"written in consultation with a leading literacy expert"
English stories
Level 1
2 13
Keywords: English stories